Oxytocin Versus Misoprostol Plus Oxytocin in the Prevention of Postpartum Hemorrhage at a Semi-Urban Hospital in sub-Saharan Africa: A Retrospective Cohort Study - Emmanuel Numfor, BSc; Nkengafac Nyiawung Fobellah, MD, MPH; Joel Noutakdie Tochie, MD; Tsi Njim, MD; Sylvester Atanga Ndesso, MSc (Global Health and Education Projects, Inc., 2020)
Background: Post-partum hemorrhage (PPH) is a leading cause of maternal mortality. Its first-line of prevention often entails uterotonic drugs like oxytocin and misoprostol which constitute a core point of management in low-resource settings of sub-Saharan Africa. This study aimed to assess the effectiveness of oxytocin alone compared with oxytocin plus misoprostol in two different eras (before and after the advert of misoprostol) of a semi-urban Cameroonian hospital. Methods: This was a retrospective cohort study carried out between January 2015 to April 2015 and between January 2016 to April 2016 on a group of parturients (group A) who received only oxytocin and another administered oxytocin and misoprostol (group B), respectively. All participants delivered at the Bamenda Regional Hospital, Cameroon. The two different periods represent the era before and after the implementation of misoprostol in the prevention of PPH in this semi-urban hospital. Socio-demographic data, clinical characteristics and details of delivery as well as risk factors for PPH were studied from obstetric records. Results: We studied the obstetric records of 1778 parturients were studied; 857 in group A and 879 in group B. Their mean age was 26.3 ±5.2 years. Both groups were comparable in several baseline sociodemographic and clinical characteristics. The prevalence of PPH was 2.7% (3.4% vs 2.2%; p = 0.0744). The risk of PPH in the oxytocin only group was about 1.5 times higher than in the oxytocin plus misoprostol group. The estimated blood loss between the two groups was statistically significant (1100 ± 150 vs 800 ± 100 ml, p< 0.0001). The active management of the third stage of labor without misoprostol was the only risk factor for PPH. Conclusion and Global Health Implications: The implementation of misoprostol plus oxytocin in the prevention of PPH in this low-resource setting improved the obstetrical outcome by reducing the risk and the amount of blood loss during delivery. Keywords: • Misoprostol • Oxytocin • Postpartum Hemorrhage • Cameroon   Copyright © 2020 Numfor et al. Published by Global Health and Education Projects, Inc. This is an open-access article distributed under the terms of the Creative Commons Attribution License (CC BY 4.0) which permits unrestricted use, distribution, and reproduction in any medium, provided the original work, first published in this journal, is properly cited.